2004
DOI: 10.1097/01.prs.0000091169.51035.a5
|View full text |Cite
|
Sign up to set email alerts
|

Selective Recruitment of Endothelial Progenitor Cells to Ischemic Tissues with Increased Neovascularization

Abstract: Tissue ischemia remains a common problem in plastic surgery and one for which proangiogenic approaches have been investigated. Given the recent discovery of circulating endothelial stem or progenitor cells that are able to form new blood vessels, the authors sought to determine whether these cells might selectively traffic to regions of tissue ischemia and induce neovascularization. Endothelial progenitor cells were isolated from the peripheral blood of healthy human volunteers and expanded ex vivo for 7 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 35 publications
0
45
0
Order By: Relevance
“…11,12 These mediators are capable of enhancing the mobilization and recruitment of EPCs to ischemic tissue during postnatal vasculogenesis. [12][13][14][15][16] In the bone mar-row, MMP-9, which is also hypoxia responsive, 17 may lead to the release of EPCs by cleavage of membrane bound kit ligand. 18,19 Interestingly, children with proliferating hemangioma have increased urinary MMP-9, 20 a finding which warrants further investigation of the role of this important mediator of stem/progenitor cell trafficking in hemangioma growth.…”
mentioning
confidence: 99%
“…11,12 These mediators are capable of enhancing the mobilization and recruitment of EPCs to ischemic tissue during postnatal vasculogenesis. [12][13][14][15][16] In the bone mar-row, MMP-9, which is also hypoxia responsive, 17 may lead to the release of EPCs by cleavage of membrane bound kit ligand. 18,19 Interestingly, children with proliferating hemangioma have increased urinary MMP-9, 20 a finding which warrants further investigation of the role of this important mediator of stem/progenitor cell trafficking in hemangioma growth.…”
mentioning
confidence: 99%
“…Consistent with an EPC phenotype, immunostaining demonstrated that most adherent cells were positive for both uptake of DiI-ac-LDL and binding of FITC-UEA-l (Fig.2) [26][27][28][29].…”
Section: Epc Characterizationmentioning
confidence: 77%
“…So, 3 days after injection, a cranially based 1.25 ϫ 2.5 cm flap, with the flap base 0.5 cm caudal to the occipital neck line, was elevated on the back of mice. A 0.13-mm-thick silicone sheet was inserted to separate the flap from the bed, and the flap was sutured in place without a dressing [3]. distance and on the same focus were taken by a digital camera.…”
Section: Pcdna31(-)/vegf165-epcs Transplantation Nude Mice Random Flmentioning
confidence: 99%
“…Some studies have been reported of augmenting the survival area of flaps using drugs, laser, hyperbaric oxygen and ischemic preconditioning, the success rate of which, however, is not satisfactory in most studies [2]. Many of the reports on augmenting the survival areas of local flaps described above are mainly directed at augmenting the blood supply to the flaps [2,3].…”
Section: Introductionmentioning
confidence: 98%